Effect of Imatinib on Bone Marrow Morphology and Angiogenesis in Chronic Myeloid Leukemia - Neetu Pandey; Geeta Yadav; Rashmi Kushwaha; Shailendra Prasad Verma; Uma Shankar Singh; Ashutosh Kumar; Prabhaker Mishra (Advances in Hematology)
Background and Objectives. Chronic myeloid leukemia (CML) is characterized by hyperproliferation of myeloid precursors, increased fibrosis, and neoangiogenesis in the bone marrow. Imatinib inhibits BCR-ABL tyrosine kinase produced due to reciprocal translocation t(9;22) in neoplastic CML cells. It reduces hyperproliferation of myeloid precursors and has been found to affect bone marrow fibrosis and angiogenesis. This study was done to assess the effect of imatinib on bone marrow morphology and angiogenesis in CML. Methods. 31 newly diagnosed CML patients were evaluated before and after 3 months of imatinib therapy. A marrow morphological response (MMR) score was used to assess marrow cytological and histological features including grade of fibrosis. Mean microvessel density (MVD) was also assessed. Hematological parameters and BCR-ABL transcript levels were assessed in the peripheral blood. Results. 86.21% of patients showed decrease in marrow cellularity with normalization of M:E ratio. 72.42% of patients had decrease in grade of fibrosis and 17.24% showed no change while 10.34% of patients showed progression of fibrosis grade. Patients with MMR score ≥ 2 (n=4) and those with progression of fibrosis grade (n=3) showed suboptimal molecular response (BCR-ABL transcripts > 10%). Pretherapy mean MVD of patients (14.69 ± 5.28) was higher than that of controls (6.32 ± 1.64). A significant reduction of 66.51% was observed in posttherapy mean MVD (4.98 ± 2.77) of CML patients (p<0.001). Conclusion. Imatinib therapy in CML not only decreases marrow cellularity, but also helps towards normalization of bone marrow microenvironment by reducing fibrosis and angiogenesis.